1992
DOI: 10.1073/pnas.89.8.3334
|View full text |Cite
|
Sign up to set email alerts
|

Galanin-mediated control of pain: enhanced role after nerve injury.

Abstract: The endogenous inhibitory role of the neuropeptide galanin in pain transmission and spinal cord excitability was demonstrated by the use of a high-affinity galanin receptor antagonist, M-35 [galanin-(1-13)-bradykinin-(2-9)-amide]. M-35, which displaced 12'I-labeled galanin from membranes of rat dorsal spinal cord with an IC50 of 0.3 nM, dose-dependently antagonized the effect of intrathecal galanin on the flexor reflex. M-35 potentiated the facilitation of the flexor reflex by conditioning stimulation of cutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
102
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(106 citation statements)
references
References 36 publications
2
102
2
Order By: Relevance
“…Fig. 4 also shows that the earlier introduced nonsubtype-specific antagonist M35 in equimolar doses antagonized the effects of galanin on the spinal flexor reflex (28).…”
mentioning
confidence: 71%
“…Fig. 4 also shows that the earlier introduced nonsubtype-specific antagonist M35 in equimolar doses antagonized the effects of galanin on the spinal flexor reflex (28).…”
mentioning
confidence: 71%
“…Pain behavior in these models is analogous to that observed in a number of human neuropathic pain conditions, including allodynia, hyperalgesia, and expansion of the receptive field. Electrophysiological experiments on axotomized (23,31), chronic constriction injury (32), and spinal nerve ligation (15) animals have shown that intrathecal administration of galanin reduces spinal cord excitability. Furthermore, intrathecal administration of the galanin antagonist M35 (31) significantly potentiates the frequency and severity of axotomy-induced autotomy behavior (33).…”
mentioning
confidence: 99%
“…The observation that galanin is also up-regulated in a variety of conditions of neuronal injury has led to the suggestion that galanin may play a role in the pathophysiology of chronic pain and Alzheimer's disease (13,14).…”
mentioning
confidence: 99%